WRITTEN FEEDBACK APPROACH: AN ALTERNATIVE WAY IN IMPROVING LEARNERS’ WRITING SKILL - Ahlan Ahlan (Universitas Lambung Mangkurat, 2021)
The researchers, teachers, and scholars have done many ways to improve learners’ writing skills. Some methods, strategies, and techniques have implemented in the classroom learning in order to improve learners’ writing. The Teaching of writing for EFL learners becomes one of a big challenge for teaching besides three language skills (speaking, reading, and listening). Factually, most of the learners still have difficulties in improving their writing. In this article, the writer recommends and discusses an alternative approach to assist learners in improving their writing. It is written feedback. The written feedback is a guide to lead learners to good writing. The writer discussed “the importance of written feedback, how teacher implements written feedback on learners’ writing skill, and the advantages of written feedback on learners' performance”.